Pengembangan Model Pembelajaran Berbasis Pendidikan Matematika Realistik Berbantuan Media Animasi untuk Meningkatkan Kemampuan Komunikasi Matematis - Meganta P, Enda Ribka; Syahputra, Edi; Ahyaningsih, Faiz (Mathematics Education Study Program, 2023)
This study aims to produce: the validity, practicality and effectiveness of learning tools based on the Realistic Mathematics Education (PMR) model, improving students' mathematical communication abilities using the developed learning tools and the process of student answers in solving mathematical communication skills questions. This research is development research with the ADDIE development model. From the results of the research, it is known that: (1) The learning model of Realistic Mathematics Education (PMR) assisted by animation media which was developed obtained an interactive learning model declared valid with an average of 4.31; (2) The Realistic Mathematics Education (PMR) learning model assisted by animation media that was developed meets the practical criteria of the learning model in terms of the analysis of the results of observations of the implementation of learning. The value obtained in trial I was 3.03 (medium category). In trial II, the score for observing the implementation of learning increased to 3.88 (category